Medications in Single-Dose Vials: Implications of Discarded Drugs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Every year, significant amounts of expensive drugs are discarded. This is due in part to the growing number of prescription drugs that are administered in variable doses (rather than fixed or flat doses) based on a patient's weight or body size. Strict regulations and guidance generally prohibit or severely restrict the acceptable time frame for sharing medication from single-dose vials among patients, and so the unused amount will typically be discarded. Due to the current system for producing, administering, and paying for drugs in the United States, significant - but indeterminate - amounts of expensive prescription drugs are discarded each year. At the request of the Centers for Medicare & Medicaid Services, Medications in Single Dose Vials: Implications of Discarded Drugs explores the federal health care costs, safety, and quality concerns associated with discarded drugs that result from the weight-based dosing of medicines contained in single-dose vials.
Keywords: Health and Medicine

Preparing the Future Workforce in Drug Research and Development: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Despite advances over the past several decades, the clinical trials enterprise has struggled to meet the needs of an increasingly diverse U.S. population. To help address this issue, a 2023 National Academies workshop sought to identify the expertise and disciplines needed to achieve the aspirations for a transformed clinical trials enterprise by 2030 and enable a workforce that can better support the evolving needs of drug R&D - one that is resilient, culturally aware, anti-racist, and interdisciplinary. The workshop, hosted by the Forum on Drug Discovery, Development, and Translation and Roundtable on Black Men and Black Women in Science, Engineering, and Medicine explored strategies to bolster workforce capacity and challenges and opportunities associated with supporting the next-generation drug R&D workforce.
Keywords: Health and Medicine

Defining and Evaluating In-Home Drug Disposal Systems For Opioid Analgesics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The proper disposal of unused or expired prescription drugs, particularly controlled substances such as opioids, may help to prevent serious risk of nonmedical use or overdose. In June 2023, the National Academies Forum on Drug Discovery, Development, and Translation hosted a hybrid public workshop to examine the scientific merit and practical implementation of drug disposal options to remove opioid analgesics from the home. Workshop participants considered potential strategies for encouraging and assessing the development and efficacy of in-home drug disposal systems that support the public health goal of mitigating the risk of nonmedical use or overdose associated with opioids.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 2021 Annual Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In 2021, the National Academies' Forum on Drug Discovery, Development, and Translation (the forum) hosted a four-part public workshop, Envisioning a Transformed Clinical Trials Enterprise: Establishing an Agenda for 2030, to set goals for the clinical trial enterprise in the year 2030 and chart a path toward those goals. The forum also completed a three-part public workshop, Innovation in Drug Research and Development for Prevalent Chronic Diseases, which brought together stakeholders to address barriers to spurring innovation for drug research and development for highly prevalent chronic diseases. Together with the National Cancer Policy Forum and the Forum on Aging, Disability, and Independence, the forum convened a three-day public workshop to identify opportunities to improve the evidence base on the effectiveness and safety of cancer therapies in adults across the older age span. For more information, please visit the forum webpage.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 2023 Annual Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
In 2023, the Forum on Drug Discovery, Development, and Translation focused on diverse topics, including approaches to define and evaluate in-home drug disposal systems for opioid analgesics, the diagnosis and treatment of adults with attention-deficit/hyperactivity disorder and implications for drug development, strategies to optimize public–private partnerships for clinical cancer research, opportunities to prepare the future workforce in research and development, and other policy updates relevant to drug discovery, development, and translation. Learn more in this 2023 Annual Review.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 2022 Annual Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Last year the Forum on Drug Discovery, Development, and Translation, helped to envision a transformed clinical trials enterprise for 2030–one that is more efficient, effective, and person-centered. In 2022, the Forum championed the inclusion of under-represented and underserved populations in clinical trials, drug research and development for adults across the older age span, and innovation in drug research and development for patients with chronic diseases. Learn more in this 2022 Annual Report.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 10 Year Review: 2011-2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
This special edition Ten-Year Review takes a look back at some of the most influential work of the National Academies' Forum on Drug Discovery, Development, and Translation over the past decade. In November 2011, amid growing concerns about the future of the U.S. clinical trials enterprise and its competitiveness on the global stage, the forum convened a public workshop for stakeholders to lay out a vision for a transformed clinical trials enterprise in the United States by 2020. This workshop laid the foundation for a variety of forum activities focused on the following thematic priorities:
Keywords: Health and Medicine

The Food and Drug Administration's Accelerated Approval Process for New Pharmaceuticals: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Accelerated approval provides a process for hastening access to innovative interventions for patients with serious or life-threatening diseases for which no other options are available. However, accelerated approval has been, at times, controversial due to uncertainties related to whether pharmaceuticals approved under the accelerated approval pathway, which relies on surrogate endpoints rather than a direct measure of clinical benefit, have met the same standards for safety and efficacy as drugs approved under the Federal Drug Administration (FDA) traditional approval pathway and whether the pathway has been used for products for which it was not intended. On January 30-31, 2023, an ad hoc committee under the auspices of the National Academies of Sciences, Engineering, and Medicine Committee on Science, Technology, and Law hosted a virtual workshop to examine the FDA accelerated approval program, one of several pathways designed to facilitate and expedite the development and review of new pharmaceuticals. This publication summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine

Harm Reduction Services for People Who Use Drugs: Exploring Data Collection, Evidence Gaps, and Research: Proceedings of a Workshop–in Brief - National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Given the public health emergency posed by drug overdoses, there have been calls for a comprehensive approach to drug policy that would include focusing on reducing harm for people who use drugs. To explore data collection efforts, evidence gaps, and research needs for harm reduction, the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop on January 30-31, 2024, sponsored by the Office of National Drug Control Policy, Executive Office of the President. The workshop focused on harm reduction strategies and services that aim to prevent overdose and infectious disease transmission; enhance the health, safety, and well-being of people who use drugs; and offer low-threshold options for accessing substance use disorder treatment. This Proceedings of a Workshop-in Brief summarizes the presentations and discussions that occurred at the workshop.
Keywords: Health and Medicine

The Security of America's Medical Product Supply Chain: Considerations for Critical Drugs and Devices: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Recent disasters and health emergencies, including the COVID-19 pandemic, have shed light on the fragility of the U.S. medical supply chain and underscored the need to explore policy, regulatory, and systems solutions to prevent and mitigate the impacts of shortages on public health, national security, and patient care. Under the Coronavirus Aid, Relief, and Economic Security (CARES) Act, the National Academies of Sciences, Engineering, and Medicine established an ad hoc committee to examine the security and resilience of the U.S. medical product supply chain. Specifically, the committee was asked to assess and evaluate the impact of U.S. dependence on critical drugs and devices sourced or manufactured outside the U.S. and provide recommendations to improve the resilience and address the vulnerabilities of the medical supply chain. On December 1 and 2, 2020, the Committee on Security of America's Medical Product Supply Chain held a two-day virtual public workshop focused on assessing lists of critical and essential medical products. The workshop sought to conceptually explore how critical and essential medical product lists are developed and used in practice. The committee's consensus study report will be available in 2022. This Proceedings of a Workshop-in Brief summarizes the discussions that occurred at the workshop.
Keywords: Health and Medicine

Assessment of Long-Term Health Effects of Antimalarial Drugs When Used for Prophylaxis - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Among the many who serve in the United States Armed Forces and who are deployed to distant locations around the world, myriad health threats are encountered. In addition to those associated with the disruption of their home life and potential for combat, they may face distinctive disease threats that are specific to the locations to which they are deployed. U.S. forces have been deployed many times over the years to areas in which malaria is endemic, including in parts of Afghanistan and Iraq. Department of Defense (DoD) policy requires that antimalarial drugs be issued and regimens adhered to for deployments to malaria-endemic areas. Policies directing which should be used as first and as second-line agents have evolved over time based on new data regarding adverse events or precautions for specific underlying health conditions, areas of deployment, and other operational factors At the request of the Veterans Administration, Assessment of Long-Term Health Effects of Antimalarial Drugs When Used for Prophylaxis assesses the scientific evidence regarding the potential for long-term health effects resulting from the use of antimalarial drugs that were approved by FDA or used by U.S. service members for malaria prophylaxis, with a focus on mefloquine, tafenoquine, and other antimalarial drugs that have been used by DoD in the past 25 years. This report offers conclusions based on available evidence regarding associations of persistent or latent adverse events.
Keywords: Health and Medicine

Drug Research and Development for Adults Across the Older Age Span: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
There is a void in evidence-based information for making informed decisions on how to optimize care for older adults, particularly those 80 years and over. Because older adults are vastly underrepresented in clinical trials, there is a dearth of information about the appropriate use of drugs in this population. Yet older adults have higher rates of comorbidities and simultaneous use of multiple medications than the general population, and are the majority users of many medications. Additionally, age-related physiological and pathological changes, particularly for adults 80 years of age and older, can lead to significant differences in the pharmacokinetics (PK)2 and pharmacodynamics (PD)3 of a given drug compared to the general population. On August 5 and 6, 2020, the National Academies of Sciences, Engineering, and Medicine hosted a workshop titled Drug Research and Development for Adults Across the Older Age Span. The workshop was designed to examine the challenges and opportunities in drug research and development for older adult populations, explore barriers that impede safety and efficacy studies in these populations, and share lessons learned for better understanding clinical pharmacology for populations over age 65. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

The Effects of Drug Control Policies on Individual and Community Health for People of Color: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The United States has a complex system of laws and policies that attempt to regulate the distribution, manufacture, and use of a variety of non-legal drug substances as part of its overall criminal justice system. Laws regarding drug use have disproportionately impacted individuals and communities of color at every step of the journey through the criminal justice system, including arrest, conviction, sentencing, and incarceration. These disparities have clear outcomes for both individual and community health. To examine the effects of drug control policies on the health of individuals and communities of color, the Roundtable on the Promotion of Health Equity held a workshop on October 8, 2018, in Washington, DC. This publication summarizes the presentations and discussions of the workshop.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 2019 Annual Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
In 2019, the National Academies’ Forum on Drug Discovery, Development, and Translation (the Forum), in collaboration with the National Academies’ National Cancer Policy Forum, hosted a meeting on Updating Labels for Generic Oncology Drugs, which provided a venue to examine the challenges and opportunities for updating labeling for generic oncology drugs. In collaboration with the National Academies’ Forum on Neuroscience and Nervous System Disorders, National Cancer Policy Forum, and Roundtable on Genomics and Precision Health, the Forum hosted two workshops:
Keywords: Health and Medicine

Innovation in Drug Research and Development for Prevalent Chronic Diseases: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Investment and innovation in drug research and development (R&D) for highly prevalent chronic diseases has stalled in recent decades, despite half of all Americans living with at least one chronic disease. As a result, prevalent chronic diseases are producing immense health care costs as well as preventable suffering and death. On February 22, March 2, and March 8, 2021, the National Academies of Sciences, Engineering, and Medicine, convened a workshop to discuss barriers to innovation in this space and examine strategies and incentives to support equitable, person-centered drug R&D for prevalent chronic diseases.
Keywords: Health and Medicine

The Role of Digital Health Technologies in Drug Development: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On March 24, 2020, a 1-day public workshop titled The Role of Digital Health Technologies in Drug Development was convened by the National Academies of Sciences, Engineering, and Medicine. This workshop builds on prior efforts to explore how virtual clinical trials facilitated by digital health technologies (DHTs) might change the landscape of drug development. To explore the challenges and opportunities in using DHTs for improving the probability of success in drug R&D, enabling better patient care, and improving precision medicine, the workshop featured presentations and panel discussions on the integration of DHTs across all phases of drug development. Throughout the workshop, participants considered how DHTs could be applied to achieve the greatest impact—and perhaps even change the face of how clinical trials are conducted—in ways that are also ethical, equitable, safe, and effective. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Stronger Food and Drug Regulatory Systems Abroad - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Ensuring the safety of food and the quality and safety of medicines in a country is an important role of government, made more complicated by global manufacturing and international trade. By recent estimates, unsafe food kills over 400,000 people a year, a third of them children under 5, mostly in low- and middle-income countries; every year poor quality medicines cause about 70,000 excess deaths from childhood pneumonia and roughly 8,500 to 20,000 malaria deaths in sub-Saharan Africa alone. The Federal Drug Administration (FDA) Office of Global Policy and Strategy is charged with improving capacity of the agency's foreign counterpart offices and increasing understanding of the importance of regulatory systems for public health, development, and trade. At the request of the FDA, this study sets out a strategy to support good quality, wholesome food and safe, effective medical products around the world. Its goal is to build on the momentum for strengthening regulatory systems and to set a course for sustainability and continued progress. The 2012 report Ensuring Safe Food and Medical Products Through Stronger Regulatory Systems Abroad outlined strategies to secure international supply chains, emphasized capacity building and support for surveillance in low- and middle-income countries, and explored ways to facilitate work sharing among food and medical product regulatory agencies. This new study assess progress made and the current regulatory landscape.
Keywords: Food and Nutrition; Health and Medicine

The Role of NIH in Drug Development Innovation and Its Impact on Patient Access: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
To explore the role of the National Institutes of Health (NIH) in innovative drug development and its impact on patient access, the Board on Health Care Services and the Board on Health Sciences Policy of the National Academies jointly hosted a public workshop on July 24–25, 2019, in Washington, DC. Workshop speakers and participants discussed the ways in which federal investments in biomedical research are translated into innovative therapies and considered approaches to ensure that the public has affordable access to the resulting new drugs. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Countering the Problem of Falsified and Substandard Drugs - Institute of Medicine (The National Academies Press, 2013)
The adulteration and fraudulent manufacture of medicines is an old problem, vastly aggravated by modern manufacturing and trade. In the last decade, impotent antimicrobial drugs have compromised the treatment of many deadly diseases in poor countries. More recently, negligent production at a Massachusetts compounding pharmacy sickened hundreds of Americans. While the national drugs regulatory authority (hereafter, the regulatory authority) is responsible for the safety of a country's drug supply, no single country can entirely guarantee this today. The once common use of the term counterfeit to describe any drug that is not what it claims to be is at the heart of the argument. In a narrow, legal sense a counterfeit drug is one that infringes on a registered trademark. The lay meaning is much broader, including any drug made with intentional deceit. Some generic drug companies and civil society groups object to calling bad medicines counterfeit, seeing it as the deliberate conflation of public health and intellectual property concerns. Countering the Problem of Falsified and Substandard Drugs accepts the narrow meaning of counterfeit, and, because the nuances of trademark infringement must be dealt with by courts, case by case, the report does not discuss the problem of counterfeit medicines.
Keywords: Health and Medicine

Drug Repurposing and Repositioning: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Drug development can be time-consuming and expensive. Recent estimates suggest that, on average, it takes 10 years and at least $1 billion to bring a drug to market. Given the time and expense of developing drugs de novo, pharmaceutical companies have become increasingly interested in finding new uses for existing drugs - a process referred to as drug repurposing or repositioning. Historically, drug repurposing has been largely an unintentional, serendipitous process that took place when a drug was found to have an offtarget effect or a previously unrecognized on-target effect that could be used for identifying a new indication. Perhaps the most recognizable example of such a successful repositioning effort is sildenafil. Originally developed as an anti-hypertensive, sildenafil, marketed as Viagra and under other trade names, has been repurposed for the treatment of erectile dysfunction and pulmonary arterial hypertension. Viagra generated more than $2 billion worldwide in 2012 and has recently been studied for the treatment of heart failure. Given the widespread interest in drug repurposing, the Roundtable on Translating Genomic-Based Research for Health of the Institute of Medicine hosted a workshop on June 24, 2013, in Washington, DC, to assess the current landscape of drug repurposing activities in industry, academia, and government. Stakeholders, including government officials, pharmaceutical company representatives, academic researchers, regulators, funders, and patients, were invited to present their perspectives and to participate in workshop discussions. Drug Repurposing and Repositioning is the summary of that workshop. This report examines enabling tools and technology for drug repurposing; evaluates the business models and economic incentives for pursuing a repurposing approach; and discusses how genomic and genetic research could be positioned to better enable a drug repurposing paradigm.
Keywords: Health and Medicine